Mulla Sadra and evolution theory - Riahi, Ali Arshad; Nassrisfahani, Mohammad; Jafarzadeh, Mehdi (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2015)
In their observations, contemporary scientists have believed in transformism which claims whole natural world is always in evolvement. This paper investigates whether Mulla Sadra’s philosophical opinions are consistent with this theory or not. The method of this research is analytical-descriptive. The conclusion is that four fundamentals: the principality of existence, the analogical unity of existence, the substantial movement and gradual increase in intensity of existence, are the main foundations of Mulla Sadra’s philosophy. The first three principles justify the forth one which is ‘the evolutional movement of the natural creatures’. According to Mulla Sadra, nature is in-itself a movement and movement is not limited to accident, but he believes that movement is the mood of the nature. He believes that nature is, therefore, a continuous whole that moves from its inferiority to its superiority, in the same way as a child grows. In this paper it is also proved that the evolution of the creatures does not contradict the existence of God and religious texts.